DILEMATIKA HUKUM PRINSIP DEKLARATIF HAK CIPTA DALAM SKEMA PEMBIAYAAN BERBASIS KEKAYAAN INTELEKTUAL - Siswoyo, Amelia Anggriany; Sutiawan, Hendrik Agus; Nasution, M.Y.F. Hafidz (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
Since 2009, creative economy has become one of the Government’s priority sectors in the national economic development effort. The creative economy sector embeds several characteristics such as intellectual creation and idea-based. Therefore, the existence of the aforementioned characteristics signifies a close relationship with the regulatory framework on intellectual property, especially in providing legal certainty towards the stakeholders, either from the perspective of the creative economy entrepreneurs as the intellectual property’s holder who may enjoy the economic benefit of their intellectual property as well as from the perspective of the investors or financial service sectors who possess the financing capability. This article specifically discusses the legal discrepancy relating to the Declarative Principle of a Creator as copyrights owner and creative economy entrepreneur in the Intellectual Property Based Financing Scheme as regulated Law No. 24 of 2019 on Creative Economy (Creative Economy Law) and Government Regulation No. 24 of 2022 on the Implementing Regulation of Law No. 24 of 2019 on Creative Economy (GR No. 24/2022) against the regulatory framework under Law No. 28 of 2014 on Copyright (Copyright Law). Keywords: Declarative Principles; Copyright; Creative Economy; Collateral.